1950
DOI: 10.1039/df9500800172
|View full text |Cite
|
Sign up to set email alerts
|

The parahydrogen conversion on palladium-gold alloys

Abstract: The activation energy of the parahydrogen conversion on palladium-rich alloys is 3-5 kcal./mole and increases abruptly between 40 and 30 atomic per cent. palladium t o the value of 8-5 kcal. found for gold-rich alloys. Magnetic measurements have identified this composition as corresponding t o the complete filling of the d-band, or atomic d-orbitals, with electrons. Vacant d-orbitals are therefore essential for the low-temperature catalysis, and it is suggested that they bond the chemisorbed hydrogen atoms M-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(28 citation statements)
references
References 0 publications
0
26
0
2
Order By: Relevance
“…Shortrange ordering in Au-Pd alloys has been reported and reviewed by Allison et al [24]. Early work on the properties of these PdAu catalysts concluded that the 0.6 d-band vacancies of pure Pd fill at an alloy composition of $60% Au, a results that stimulated studies of the catalytic properties of Au-Pd mixtures at this critical composition, e.g., ortho, para-hydrogen conversion [30]. However, in surveying a number of reactions, the consensus is that surface composition is more important for adsorption and catalysis than is the bulk electronic structure [12,24,[31][32][33][34].…”
Section: Catalysis By Pd-aumentioning
confidence: 96%
“…Shortrange ordering in Au-Pd alloys has been reported and reviewed by Allison et al [24]. Early work on the properties of these PdAu catalysts concluded that the 0.6 d-band vacancies of pure Pd fill at an alloy composition of $60% Au, a results that stimulated studies of the catalytic properties of Au-Pd mixtures at this critical composition, e.g., ortho, para-hydrogen conversion [30]. However, in surveying a number of reactions, the consensus is that surface composition is more important for adsorption and catalysis than is the bulk electronic structure [12,24,[31][32][33][34].…”
Section: Catalysis By Pd-aumentioning
confidence: 96%
“…It has also been suggested that exchange may occur via triatomic intermediates. These two mecha-nisms are usually referred to as the Bonhoeffer-Farkas and the Rideal-Eley mechanisms [11,12]. The former has been observed to be operative usually at higher temperatures whereas the latter, involving intermediates, is operative only at low temperatures.…”
Section: Surface Kinetics Of Hydrogen Permeation In Mixed Proton-elecmentioning
confidence: 99%
“…The reaction takes place between reactant from the gas phase and an adsorbed one (Scheme 1.2). The Eley-Rideal mechanism well describes the kinetics of the hydrogen-deuterium reaction [10].…”
Section: Mechanisms In Gas/solid Heterogeneous Catalysismentioning
confidence: 99%